Morfologia e silvicultura de espécies arbóreas da floresta estacional decidual - Felippi, Marciele (2010)
The morphological and silvicultural of Apuleia leiocarpa (Vogel) J. F. Macbr. (Grápia) Cabralea canjerana (Vell.) Mart. (Canjerana), Cordia trichotoma (Vell.) Arrab. ex Steud. (louro), Holocalyx balansae Micheli (alecrim) and Diatenopteryx sorbifolia Radlk. (maria-preta) was conducted from March 2007 to March 2010, in the City of Frederico Westphalen and in conditions of laboratory and forest nursery, located in the Federal University of Santa Maria, Rio Grande do Sul. In that way, were selected 20 matrixes trees of each species for observations of flowering and fruiting, collection of flowers, fruits and seeds for morphological description and to quantify the number of seeds per kilogram, germination, emergence and description and illustration of the germination process, plantlent and seedling . Seeds of grápia and canjerana were analyzed from each mother tree that has had ripe fruit in the same period, while for the others, was formed a portion of seeds depending on the irregularity of production. For maria preta, took place just phenological and morphological description. The species showed the phenophases influenced by environmental variables and temperature, having irregularity in the production of fruits and seeds according to the year and tree matrix. The increased presence of grápia flowers occurred from September to October; canjerana from September to October; louro from February to June; alecrim in two occasions, February and from June to September, and maria preta from September to October. The fruit ripening was more intense from January to March for grápia; canjerana from November to January, May to July for louro, November and March-April for alecrim, and from November to January for maria preta. The study highlights new morphological information and illustrations of flowers, fruits, seeds, seed germination until the seedling stage, emphasizing the variations noticed in size of fruits and seeds. There were significant differences of seeds from matrix trees of grápia and canjerana, in physical and physiological tests, as well as, low germination rate from the portion seeds of louro and alecrim. After the implementation in the field, seedlings of grápia and canjerana from different mother trees, showed variations in growth and survival. The data obtained allow practical application in ecological studies, germination tests, seedling production, among others, increasing the importance of using seeds acquired from a larger number of matrixes, considering the wide variation of results achieved.